Guanylins - Agents with natriuretic effect - Solichova, Pavlina; Stejskal, David; Proskova, Jitka (Biomedical papers, 2006)
Guanylins and uroguanylins are natriuretic peptides with different effects in many of tissues. In context with guanylins, the intestine-renal axis is presented. The overproduction of guanylin or uroguanylin leads to secondary diarrhea with stimulation of Cl- secretion. A diet high in salt lead especially to increased guanylin and uroguanylin secretion. Interesting applications with guanylins measurement could to be in hypertension diagnosis, monitoring of heart dysfunction treatment, intensive care etc.
Keywords: cGMP/G-C family/Guanylins/Proguanylin/Uroguanylin